2019
DOI: 10.1038/s41598-019-42203-z
|View full text |Cite
|
Sign up to set email alerts
|

Moderate exercise improves function and increases adiponectin in the mdx mouse model of muscular dystrophy

Abstract: The loss of dystrophin produces a mechanically fragile sarcolemma, causing muscle membrane disruption and muscle loss. The degree to which exercise alters muscular dystrophy has been evaluated in humans with Duchenne Muscular Dystrophy (DMD) and in mouse models including the mdx mouse but with inconsistent findings. We now examined two different levels of exercise, moderate and low intensity, in the mdx mouse model in the DBA2J background. mdx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“… 25 One of the key outcomes for gene therapy, therefore, should be the rescue of diaphragm function, as respiratory failure often leads to death. 25 In the absence of treatment, moderate treadmill exercise improves respiratory function in mdx-DBA/2J mice, 48 while in contrast, impaired diaphragm function in mdx mice after 52 weeks of running yielded an ∼60% decline compared to sedentary controls. 15 Treatment with microdystrophin in mdx mice at least partially rescued muscle strength and resistance to eccentric injury in both limb and diaphragm muscles.…”
Section: Discussionmentioning
confidence: 99%
“… 25 One of the key outcomes for gene therapy, therefore, should be the rescue of diaphragm function, as respiratory failure often leads to death. 25 In the absence of treatment, moderate treadmill exercise improves respiratory function in mdx-DBA/2J mice, 48 while in contrast, impaired diaphragm function in mdx mice after 52 weeks of running yielded an ∼60% decline compared to sedentary controls. 15 Treatment with microdystrophin in mdx mice at least partially rescued muscle strength and resistance to eccentric injury in both limb and diaphragm muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Replenishment of ApN by transgenesis mitigated the dystrophic phenotype by attenuating inflammation while improving regeneration, muscle function, and physical performance . Likewise, increasing serum ApN by moderate exercise was associated with improved muscle function in mdx mice . On the contrary, complete depletion of ApN levels greatly aggravated the phenotype .…”
Section: Discussionmentioning
confidence: 96%
“…Further, with age, mdx mice had greater diaphragm muscle atrophy and fibrosis, leading to increased respiratory impairment compared to WT mice [ 55 57 ]. Previous work assessing ventilatory function in mdx mice using WBP has been predominantly performed with males [ 58 60 ], with some studies pooling male and female mice [ 41 , 61 ], or with sex not reported [ 62 ]. This study is the first that we know of to report ventilatory function in only female mdx mice across ages.…”
Section: Discussionmentioning
confidence: 99%